Factors associated with post-stroke depression and emotional incontinence: lesion location and coping styles. (2nd July 2016) - Wei, Changjuan; Gao, Juan; Chen, Li; Zhang, Fang; Ma, Xiaofeng; Zhang, Nan; Zhang, Wei; Xue, Rong; Luo, Lanlan; Hao, Junwei
Abstract : Post-stroke depression (PSD) and post-stroke emotional incontinence (PSEI) have attracted worldwide interest in recent years. These emotional disturbances have a negative impact on the rehabilitation process and the associated worse outcome. Consequently, defining the risk factors for development of PSD and PSEI is important. In this study, we evaluated 368 consecutive patients with acute ischemic stroke at admission and at three months later. PSD was evaluated by using the Beck Depression Inventory, and PSEI was evaluated using Kim's criteria. The Social Support Rating Scale and Medical Coping Modes Questionnaire were also used as measurement tools. Multivariate analyses showed that anterior cortex infarction was associated with PSEI three months after stroke occurrence. The appearance of PSD was not related to lesion location. Both motor and sensory dysfunctions was independently associated with PSD at admission, whereas low degree of social utilization was the independent factor associated with PSD 3 months after stroke. Acceptance-resignation is related to PSD and PSEI both at admission and 3 months after stroke. Avoidance was the independent factor related to PSD at 3 months after stroke onset.